What can language biographies reveal about multilingualism in the Habsburg Monarchy? A case study on the members of the Illyrian Movement - Novak, Kristian (2011)
The reconstruction of language biographies of the Illyrian movement mebers was based on their available, published or unpublished, texts written in all of the idioms they were using (Croatian dialects and literary languages, German, Latin). The focus of this research was primarily on journal and autobiographical entries and private correspondence, containing reflections on personal attitudes towards their own language behaviour and the language reality of their social environment. The aim of this research was to gather, from a micro-perspective, information about the dynamics of macro-level sociolinguistic developments in the first half of the 19th century, primarily focusing on German-Croatian bilingualism and the deliberate switch from the Kajkavian to the supra-regional Štokavian literary language in north-western Croatia.